Improving Voluntary Tax Compliance: The Role of Account Representatives’ Quality Services - Khoiriawati, Novi -; Mashudi, Mashudi; Meirini, Dianita; Muhammadi, Qasem (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study examines the mediating role of taxpayer’s satisfaction in the relationship between service quality of account representative and voluntary tax compliance. The research employed a quantitative approach with a survey method. The data were collected by distributing questionnaires to 327 taxpayers who had previously consulted with an account representative. Structural equation modelling (SEM) using AMOS Graphics was employed to analyse the data. The research results showed that the service quality of account representatives and taxpayer satisfaction had positive and significant effects on voluntary compliance. This study also found that taxpayer satisfaction does not mediate the relationship between the service quality of account representatives and voluntary. This was because tax payments are compulsory and based on law, so whether the taxpayers are satisfied with the service of the account representative does not affect their compliance in paying the taxes.